Strategie e tecniche per leggere ad alta voce a scuola 16 suggerimenti per insegnanti del primo e del secondo ciclo - Batini, Federico; Giusti, Simone (FrancoAngeli, 2022)
The book is intended as an operational tool for all teachers at all school levels who want to contribute to the introduction of reading aloud in schools in an intensive, progressive and daily fashion. The book makes use of the research work carried out within the "Reading: So Cool!" project in the Region of Tuscany. In the first year, training, supervision, support, monitoring and quantitative and qualitative surveys were focused on the 0/6 system which the first book, divided into 27 suggestions for reading aloud, addressed (Batini, Giusti, eds., 2021). The present volume represents the continuation of the second year of the research and illustrates 16 fundamental techniques and strategies for correct management of the practice of reading aloud in the school context. The methodological proposals are organised in three sections: Preparation, Action! and After Reading. This volume is the result of a participatory process involving fruitful dialogue among the scientific literature, expertise and didactic practice and in which the experience of a panel of experts - composed of scholars, operators, educators and teachers of all school levels - has been enhanced. "Reading: So Cool! Reading aloud increases intelligence" is an educational policy of the Region of Tuscany, implemented with the scientific and operational coordination of the University of Perugia (Department of Philosophy, Social Sciences and Education), in collaboration with Cepell ("Centre for Promotion of Books and Reading" of the Ministry for Cultural Heritage and Activities); the Regional School Office of Tuscany; Indire (Central Institute for Innovation, Documentation and Educational Research); and LaAV (National movement of reading aloud volunteers within the association Nausika).